2017
DOI: 10.1038/ctg.2017.49
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Impedance and Pepsin Detection in the Laryngeal Mucosa to Determine Impedance Values that Indicate Pathological Laryngopharyngeal Reflux

Abstract: Objective:Recently, a 24-h impedance was used to detect laryngopharyngeal reflux (LPR). However, not every case of LPR is pathological. Thus, pathological pharyngeal impedance values need to be clearly established to diagnose pathological LPR. The aim of our study was to establish pathological 24-h pharyngoesophageal impedance/pH values for the diagnosis of LPR.Methods:The study was conducted in a tertiary care setting. A total of 30 patients who were referred to microlaryngoscopy for a laryngeal pathology tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…This approach was developed according to some studies, which reported that the deposit of pepsin on the laryngopharyngeal mucosa leads to the development of mucosal inflammation and injury and the related symptoms and signs . Peptest (RD Biomed) provides a measurement of the pepsin saliva concentration, which theoretically is correlated with the occurrence of pharyngeal/proximal esophageal reflux episodes within the previous hours . However, no studies have investigated the association between the occurrence of proximal LPR episodes and the saliva pepsin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was developed according to some studies, which reported that the deposit of pepsin on the laryngopharyngeal mucosa leads to the development of mucosal inflammation and injury and the related symptoms and signs . Peptest (RD Biomed) provides a measurement of the pepsin saliva concentration, which theoretically is correlated with the occurrence of pharyngeal/proximal esophageal reflux episodes within the previous hours . However, no studies have investigated the association between the occurrence of proximal LPR episodes and the saliva pepsin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the close proximity of the monitor sensor to the oral pharynx/oral cavity, which is a short distance for the refluxate to travel from laryngopharynx to the oral cavity. Numerous investigations in adults have clearly demonstrated that salivary pepsin A associated with MII‐pH probe detected laryngopharyngeal reflux 21‐23 . The role of saliva pepsin A in diagnosing gastro‐oesophageal reflux needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations in adults have clearly demonstrated that salivary pepsin A associated with MII-pH probe detected laryngopharyngeal reflux. [21][22][23] The role of saliva pepsin A in diagnosing gastro-oesophageal reflux needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The original 'gold-standard' for LPR diagnosis was dual channel 24-h pH monitoring which lacks sensitivity and specificity due to its inability to detect nonacidic reflux events [9]. However, this has been somewhat superseded as the 'gold-standard' by MII-pH monitoring and there have been several studies published describing the use of MII-pH in monitoring and detection LPR [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%